Non-negotiable : why moral naturalism cannot do away with categorical reasons - Luco, Andrés Carlos (2021)
Some versions of moral naturalismare faulted for implausibly denying that moral obligations and prescriptions entail categorical reasons for action. Categorical reasons for action are normative reasons that exist and apply to agents independently of whatever desires they have. I argue that several defenses of moral naturalism against this charge are unsuccessful. To be a tenable meta-ethical theory, moral naturalism must accommodate the proposition that, necessarily, if anyone morally ought to do something, then s/he has a categorical reason to do it. Versions of moral naturalism that deny this claim would, if widely believed, disable some crucial practical uses of moral concepts. In particular, if the existence of normative reasons for action is taken to be dependent on agents’ desires, it would breed profound skepticism about the legitimacy of evaluating others’ actions from a moral point of view. Also, it would raise doubts about whether people ought to correct their own behavior in light of moral considerations. Following Richard Joyce, I take these consequences to indicate that the concept of a categorical reason is a ‘‘non-negotiable’’ part of moral concepts.